GRK5 Controls SAP97-Dependent Cardiotoxic β1 Adrenergic Receptor-CaMKII Signaling in Heart Failure. Issue 6 (28th August 2020) - Xu, Bing; Li, Minghui; Wang, Ying; Zhao, Meimi; Morotti, Stefano; Shi, Qian; Wang, Qingtong; Barbagallo, Federica; Teoh, Jian-Peng; Reddy, Gopireddy R.; Bayne, Elizabeth F.; Liu, Yongming; et al.
Abstract : Rationale: Cardiotoxic β1 adrenergic receptor (β1 AR)-CaMKII (calmodulin-dependent kinase II) signaling is a major and critical feature associated with development of heart failure. SAP97 (synapse-associated protein 97) is a multifunctional scaffold protein that binds directly to the C-terminus of β1 AR and organizes a receptor signalosome. Objective: We aim to elucidate the dynamics of β1 AR-SAP97 signalosome and its potential role in chronic cardiotoxic β1 AR-CaMKII signaling that contributes to development of heart failure. Methods and Results: The integrity of cardiac β1 AR-SAP97 complex was examined in heart failure. Cardiac-specific deletion of SAP97 was developed to examine β1 AR signaling in aging mice, after chronic adrenergic stimulation, and in pressure overload hypertrophic heart failure. We show that the β1 AR-SAP97 signaling complex is reduced in heart failure. Cardiac-specific deletion of SAP97 yields an aging-dependent cardiomyopathy and exacerbates cardiac dysfunction induced by chronic adrenergic stimulation and pressure overload, which are associated with elevated CaMKII activity. Loss of SAP97 promotes PKA (protein kinase A)-dependent association of β1 AR with arrestin2 and CaMKII and turns on an Epac (exchange protein directly activated by cAMP)-dependent activation of CaMKII, which drives detrimental functional and structural remodeling in myocardium. Moreover, we have identified that GRK5 (G-protein receptor kinase-5) is necessary to promote agonist-induced dissociation of SAP97 from β1 AR. Cardiac deletion of GRK5 prevents adrenergic-induced dissociation of β1 AR-SAP97 complex and increases in CaMKII activity in hearts. Conclusions: These data reveal a critical role of SAP97 in maintaining the integrity of cardiac β1 AR signaling and a detrimental cardiac GRK5-CaMKII axis that can be potentially targeted in heart failure therapy. Abstract : Supplemental Digital Content is available in the text.